Genotoxicity and Toxicity Assessment of a Formulation Containing Silver Nanoparticles and Kaolin: An In Vivo Integrative Approach - Adriana Rodriguez-Garraus; María Alonso-Jauregui; Ana-Gloria Gil; Iñigo Navarro-Blasco; Adela López de Cerain; Amaya Azqueta (Nanomaterials, 2022)
A new material composed of a kaolin base with silver nanoparticles (AgNPs) attached to its surface was developed, as an alternative to antibiotics used as supplements in animal feed. As part of its safety assessment, an in vivo geno-toxicological evaluation of this material was conducted in rats. First, a preliminary dose finding study was carried out to decide the doses to be tested in the main study: 50, 300 and 2000 mg/kg b.w. For the main study, a combined strategy composed of the MN test (TG 474) and the comet assay (TG 489), integrated in a repeated dose 28-day oral toxicity study (TG 407), was performed. A No Observed Adverse Effect Level (NOAEL) of 2000 mg of the silver-kaolin formulation/kg b.w. by oral route, for 28 days, was determined. The silver-kaolin formulation did not induce micronuclei in bone marrow, or DNA strand breaks (SBs) or alkali labile sites (ALS) in liver, spleen, kidney or duodenum at any dose. The modified Fpg comet assay did not reveal oxidized bases in the same tissues at the dose of 2000 mg/kg b.w. Silver was quantified by ICP-MS in all the target organs, confirming the negative results obtained under these conditions.